Numerical and experimental investigation of an internally pinned heat exchanger with regression modeling for thermal performance prediction - Aich, Walid; Alshammari, Yasser Munif; Almuballi, Mohammed Khalid; Ayadi, Badreddine; Ben Said, Lotfi; Alshammari, Badr M.; Kolsi, Lioua (Wiley-V C H Verlag Gmbh, 2025)
A novel heat exchanger design featuring internally mounted pins is the subject of the current study. The aim is to enhance the thermal performance without significantly increasing the pressure drop. Three pin arrangements; linear, square, and triangular, were numerically analyzed using Computational Fluid Dynamics (CFD) simulations based on the Finite Element Method (FEM). The triangular configuration is found to have the most efficient heat transfer characteristics compared to the other ones and was subsequently selected for fabrication and experimental validation. The manufactured heat exchanger was tested under various flow rates and inlet temperatures. The Results showed that there is a strong agreement between numerical and experimental data, and the discrepancies are attributed to actual heat losses. In addition, using the obtained data, a regression model based on a power-law correlation was developed to predict the overall heat transfer coefficient, achieving high accuracy with an R 2 of 0.9865 and RMSE of 24.78 W/m2K. These findings confirm the potential of internally pinned configurations for compact and efficient thermal systems in industrial applications.
Keywords: Fins; Optimization